Supplements consumption, health oriented behaviour and beyond - Viscecchia, Rosaria; De Devitiis, Biagia; Baselice, Antonio; Stasi, Antonio; Nardone, Gianluca (Italian Review of Agricultural Economics, 2016)
The dietary supplements use is constantly growing as proof that people pay always more attention to their diet and their physical status. Italy recorded the highest growth in the European market within 2008 and 2012. The reasons and the factors behind the consumption of dietary supplements are complex, combining social, psychological, knowledge and economic factors. In order to provide consumers’ profiles and to estimate the following relationship between them and the socio-demo, lifestyle, health-related behaviour, a survey study was conducted on a sample of 400 Italian consumers. The main results highlight the presence of four different profiles, distinguished mainly by different lifestyle, health needs and self-perceived health status. Through a logit regression it was also estimated the probability to consume the different categories of supplements for each profile. In this way, this study could provide useful hints to implement public health guidelines and to avoid a no-proper use of supplements.